PERCEPTION OF ADOLESCENT TO DYSMENORRHEA IN STUDENT WOMEN OF DISTRICT BANYUMANIK SEMARANG CITY - Mubarokah, Esti; Yuliawati, Sri; Udiyono, Ari; Wagiran, Wagiran (Jurnal Ilmiah Ilmu Kesehatan: Wawasan Kesehatan, 2017)
Dysmenorrhea is the most common of gynecologic complaints. Adolescence is transisional period, requiring information about why and how dysmenorrhea occurs. Lack information leads to misconception, which will aggravate pain and improvement of dysmenorrhea. The results of preliminary survey, November-October 2013 Tembalang, Semarang 81.8% women experience dysmenorrhea. The aim of this study is correlation between the perception with degree of dysmenorrhea. This study uses quantitative method and extract information qualitative, observational analytic cross sectional, conducted on 150 senior high school from class XI (15-17 years) in District Banyumanik Semarang. Instruments consist of four sections, they are characteristics of respondents, knowledge, perception, are using questionnaire and the degree of dysmenorrhea using visual analogue scale (VAS). Sampling carried out consecutively. Chi-square test were conducted to determine the association among variables. The mean age menarche and age in adolescent 13 and 16 years. Adolescent knowledge about dysmenorrhea less (73.3%), the average education of adolescent mothers finish senior high school (37,3%). Approximately 66% used reliever, and 6,7% school absenteeism. The prevalence of dysmenorrhea 94,7%, approximately 16,7% have severe dysmenorrhea. While 50% respondents have negative perception. Statistical test (Î± = 5%) shows the relationship between perceptions with degree of dysmenorrhea (pOR=3,068: CI=1,20-7,86; p-value=0,016). Dysmenorrhea pain is often lost after taking drugs. This needs to be done to reduce the impact of dysmenorrhea with psychotherapy